Effect of Web Flexibility in Gear Engagement: A Proposal of Analysis Strategy - Fabio Bruzzone; Carlo Rosso (Vibration, 2022)
Increasing torque and power density in geared transmissions is a constant trend, especially due to the electrification and the research of higher efficiency. Thinner web of the gears has led to potentially higher vibration amplitudes and noise levels, which need to be accounted for in the design stage to avoid fatigue or NVH problems. In the present paper a novel model to represent the dynamic interaction in geared transmissions is presented. The compliances of the shafts are taken into account in two different ways: in a simple strategy, by means of three-dimensional beam elements; in a more detailed methodology, by reduction in a FE model of the gear and shaft assembly. The different gears are connected using kinematic relationships exploited by means of rigid joints and rigid body elements. The flexibility of the teeth and of the gear body is introduced based on an established nonlinear calculation model and is employed as the only dynamic excitation source as a time varying mesh stiffness. Thanks to the reduced size of the matrices a direct integration scheme is used for the time domain analysis of the transmission. Such methodology enables the possibility of modeling dynamic contact loss and torque variations at different rotational velocities with reduced computational times in comparison to other approaches. The technique is then applied to two different geometries of driven gear: one with solid web and one with flexible web. The dynamic behavior of the two different solutions is studied and the differences are highlighted. The proposed approach proves to be more efficient than traditional multibody analyses and quicker than finite element approaches, while maintaining a similar accuracy. It proves to be effective also for studying the transmission with flexible web.